Relationship between long non-coding RNAs and Hippo signaling pathway in gastrointestinal cancers; molecular mechanisms and clinical significance - Farimah Fayyaz; Zahra Shokati Eshkiki; Amir Reza Karamzadeh; Zahra Moradi; Faezeh Kaviani; Abolfazl Namazi; Roya Karimi; Seidamir Pasha Tabaeian; Fatemeh Mansouri; Abolfazl Akbari (Heliyon, 2024)
Long non-coding RNAs (lncRNAs) play a significant biological role in the regulation of various cellular processes such as cell proliferation, differentiation, apoptosis and migration. In various malignancies, lncRNAs interplay with some main cancer-associated signaling pathways, including the Hippo signaling pathway to regulate the various cellular processes. It has been revealed that the cross-talking between lncRNAs and Hippo signaling pathway involves in gastrointestinal (GI) cancers development and progression. Considering the clinical significance of these lncRNAs, they have also been introduced as potential biomarkers in diagnostic, prognostic and therapeutic strategies in GI cancers. Herein, we review the mechanisms of lncRNA-mediated regulation of Hippo signaling pathway and focus on the corresponding molecular mechanisms and clinical significance of these non-coding RNAs in GI cancers.